Nobody Knows – Towards Operationalization of Strategic Dilemmas of Coopetitors - Patrycja Klimas; Joanna Radomska (European Management Studies)
Purpose: This paper presents an operationalization framework that merges the concepts of coopetition and open strategy through the lenses of managerial dilemmas. Although both merged concepts have gained recent and increasing attention, they need sound operationalization, including operationalization when being blended. Therefore, the paper focuses on operationalizing and measuring strategic dilemmas of coopetition implemented as an open strategy. By doing so, the paper addresses the needs for developing measures and scales to allow for more detailed investigation and verification of the conceptual foundations of open strategy dimensions and accompanying tensions and paradoxes of coopetition. Design/methodology/approach: This paper is conceptual. Our proposition for operationalization builds on previously developed conceptualizations of strategic dilemmas and strategic choices considered. Findings: As the main contribution, this paper offers comprehensive operationalizations for seven strategic dilemmas faced by coopetitors following an open approach to strategy implementation. Research limitations/implications: The paper draws managers’ attention to the multidimensional perception of strategic dilemmas faced when cooperating with competitors and provides a way to analyze the profile of openness, which can be used to evaluate a firm’s openness as well as to predict coopetition longevity. Originality/value: The contribution of our conceptual framework is twofold as we advance the concept of merging coopetition with an open strategy using the lenses of managerial dilemmas that are commonly faced in both conceptions.